Correlation of Likert scores III–V with increasingly worse pathology in radical prostatectomy specimens significant only for men aged <60 or PSAD >0.15, with age <60 as good as PSAD <0.15 at discriminating lower risk in Likert III. (January 2023) - Ord, Jonathan J; Crockett, Matthew; Green, Jes; Bell, Lawrence TO; Hicks, Victoria; Crawford-Smith, Hugh; Morss, Amanda; Poulton, Lucinda; Pellisery, Bilgy; Hayes, Mark; Ludeman, Linmarie; Beasley, Matthew; et al.
Objectives: This study aimed to compare Likert scores with radical prostatectomy specimens. Methods: This study examined 443 men with validated pre-biopsy magnetic resonance imaging results and used cross-tabulation and chi-square significance testing with National Comprehensive Cancer Network risk categories. Results: The mean prostate-specific antigen (PSA) was 10, and the mean age was 64 years. Comparing Likert III to Likert V and Likert IV to Likert V, both (each p =0.02) were significantly associated with higher prostate cancer risk groups, but Likert III versus Likert IV was not ( p =0.1). Within the subgroup PSA density (PSAD) <0.15 ( n =140), the correlation of Likert score and final pathological risk group was lost ( p =0.5), but it was not lost within the subgroup PSAD >0.15 ( n =281; p =0.045 III vs. IV only and p =0.055 overall). Within the subgroup age <60 ( n =104), the correlation of Likert score and final pathological risk group was significant ( p =0.006 for III vs. IV and p =0.04 overall), whereas within the subgroup age >60 ( n =339) this significant difference was lost ( p =0.34). Further subgroup analysis within Likert III ( n =86) found that men <60 ( n =22) had neither high-grade (G3 or G4 or G5) nor very high-risk disease. There were only two high-risk cases, both of which were G2T3a (2/22; 10%). In men with Likert III and PSAD <0.15 ( n =31), there were seven high-risk and two very high-risk cases (9/31; 25%). This difference was not significant ( p =0.31) Conclusion: With these two findings, we recommend that men <60 with Likert III can be counselled like men with Likert III and PSAD <0.15, that they are unlikely to have unfavourable or high-risk disease and that they may wish to avoid biopsy or treatment. Level of evidence: Level 1b.